Decentralized Multi-robot Collision-free Path Following Based on Time-varying Artificial Vector Fields and MPC-ORCA - Freitas, Elias J. R.; Vangasse, Arthur Da C.; Raffo, Guilherme V.; Pimenta, Luciano C. A. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This work focuses on the solution for multi-agent, collision-free, time-varying path-following problems in 3D spaces. The proposed solution is based on using time-varying artificial vector fields to generate velocity references for single agents. A distributed Model Predictive Control (MPC) scheme is employed, taking into account the system’s dynamics and collision avoidance features, enabling the multi-robot system to follow the dynamic field without collisions and providing great computational efficiency. More specifically, Optimal Reciprocal Collision Avoidance (ORCA) algorithm is used to set constraints, yielding a novel MPC-ORCA approach, for efficient collision avoidance in the multi-agent scenario. Simulation scenarios are used to validate and compare the proposed approach with traditional methods, highlighting its improvements.